The effect of applying total quality management on the competitiveness from the point of view of the front-rows employees for customer service (An analytical study of Palestinian local banks) - awad, Azmi wasfi (Journal of Economics and Administrative Sciences, 2020)
The study aimed to identify the effect of Total Quality Management on enhancing competitiveness through the opinions of employees of the front- rows of customer service in local Palestinian banks, the researcher adopted an analytical descriptive method through developing a special questionnaire to accomplish the study’s objectives and answer its questions. The study involved all the Palestinian local banks, with their scattered branches in West Bank. The study sample consisted of 3470 executive employees for banking services out of 4753 employees, in the rate of 73%, and the study sample reached (485) employees who were randomly selected working in the front -rows to provide services in the local Palestinian banks during the year 2019, And the added value in this study was to examine the opinion of that sample of respondents, The results showed statistically significant differences for the importance of applying TQM and competitiveness. Based on the results of the study, the researcher recommended Palestinian local banks to deepen the employment of Total Quality Management in all its dimensions in their banking services to enhance their competitive capabilities. And to focus on developing and refining the skills of employees, developing and diversifying banking services based on modern technology, and measuring the quality of service provided to customers on a regular basis and in various forms and methods.